Consuming a mixed diet enriched with lupin protein beneficially affects plasma lipids in hypercholesterolemic subjects: A randomized controlled trial - Bähr, Melanie; Fechner, Anita; Kiehntopf, Michael; Jahreis, Gerhard (Clinical nutrition (Edinburgh, Scotland), 2015)
The objectives of this study were to assess whether 25 g/d lupin protein, integrated into a mixed diet, might affect cardiovascular risk factors and whether l-arginine was responsible for these effects. Seventy-two hypercholesterolemic subjects participated in the randomized, controlled, double-blind three-phase crossover study. They were assigned to three diets with 25 g/d lupin protein (LP), milk protein (MP) or milk protein plus 1.6 g/d arginine (MPA) each for 28 d in a random order interrupted by 6-week washout periods. Lupin protein and the comparator milk protein were incorporated into complex food products (bread, roll, sausage, and vegetarian spread). Arginine was administered via capsules. Sixty-eight subjects were included in final analyses. Compared with MP, LDL cholesterol was significantly lower after LP. Compared with MP and MPA, homocysteine was significantly lower after LP. Compared with baseline, concentrations of total, LDL, and HDL cholesterol significantly decreased after LP and MPA. Triacylglycerols and uric acid significantly decreased after LP. The relative changes in total and LDL cholesterol were significantly greater for subjects with severe hypercholesterolemia (>6.6 mmol/L) than those with moderate hypercholesterolemia (5.2–6.6 mmol/L). The present study showed for the first time that incorporation of 25 g/d of lupin protein into a variety of complex food products lowers total and LDL cholesterol, triacylglycerols, homocysteine, and uric acid in hypercholesterolemic subjects. The hypocholesterolemic effect is stronger in subjects with severe hypercholesterolemia. Arginine might be responsible for some, but not all of the beneficial effects of lupin protein. This trial was registered at http://clinicaltrials.gov (study ID number NCT01598649).